Aristóteles, el mal moral y el pecado - Oriol Salgado, Manuel (Cauriensia, 2023)
Though it is true that the philosophical problem of evil is not one of the central topics in classical Greek philosophy, we can find some insightful reflections on it. The first aim of this paper is to examine the problem of moral evil in Aristotle, specifically in the Nicomachean Ethics. For this purpose, we will approach the general framework of Aristotelian ethics and the role that the study of vice plays in it, as opposed to the study of virtue, as well as other moral dispositions. Next, we will distinguish the different moral characters that can be qualified as evil (vice, akrasia and bestiality), making a summary of their main features. The second aim is a comparison between the Christian concept of sin and the Aristotelian treatment of moral evil. We will begin by highlighting the similarities, and then we will find some essential differences, focusing on the significance, scope, responsibility and overcoming of moral evil.